Argumentation from the theology verses by the methode of the Qur'an and Sunnah | الاستدلال من الآيات الألوهيات على نهج القرآن والسنة - Sofiyulloh Mukhlas (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2010)
This research is about theology study based on the Quran and Surn1ah. Thiss udy concluded that argumen tation about theology must be based on themethodology of al-Quran and Hadith. Wrong method or contradictive methodto the two sources of Islamic law is not only effect in misunderstanding, but itcan bri.. someone to become disbeliever. TI1e object of this research is makingthe Qur an as the basic of study, as well as feature of the study. Furthermore,this study used descriptive method with both classical and modem references.